EFFECT OF TREATMENT OF VARIOUS PHYSICAL SCARIFICATIONS AND CONCENTRATION LEVELS OF POTASSIUM NITRATE SOLUTION (KNO3) ON THE GERMINATION OF MOUNTAIN SOURSOP SEEDS (Annona montana Macfad) - Aliffia Pratiwi; Yayu Romdhonah; Dewi Ayu Lestari; Nur Iman Muztahidin; Imas Rohmawati (Sean Institute, 2023)
This study aimed to determine the effect of various physical scarification and the level of potassium nitrate (KNO3) concentration on the germination of mountain soursop (Annona montana Macfad) seeds. This research was carried out at the Research Greenhouse in Purwodadi Botanic Garden, Research Center of Plant Conservation, Botanic Garden and Forestry, National Research and Innovation Agency from January to March 2022. The study used a randomized block design (RBD) which was arranged in a factorial manner and consisted of two factors. The first factor was various physical scarification of the seeds (without scarification, scratching, shearing, and sanding). The second factor was the concentration level of the KNO3 solution (0,2%, 0,4%, and 0,6%). There were 12 combinations with 3 replications so there were 36 experimental units. The parameters measured were germination age (days), normal germination percentage (%), abnormal germination percentage (%), maximum growth potential (%), germination capacity (%), and growth rate (%/day). The results showed that sanding physical scarification gave the best affect on parameter germination age (days) and germination capacity (%) of mountain soursop seeds. The concentration level of the KNO3 solution 0,6% gave the best affect for all parameters observed of mountain soursop seeds. There was no interaction between physical scarification and concentration level of the KNO3 solution for all parameters observed of mountain soursop seeds.